Digital Economics in Motion: Analyzing UTAUT Factors Driving Payment Gateway Adoption Among Bali’s MSMEs - Yulianingsih, Ni Nyoman Vera; Korry, Putu Dyah Permata (International Journal of Economics Development Research (IJEDR), 2025)
This study discusses the digital transformation of Micro, Small, and Medium Enterprises (MSMEs) in Bali, focusing on the influence of the UTAUT concept on the interest in using payment gateways among entrepreneurs. The background of this study emphasizes the importance of adopting digital technology to support the economic growth of MSMEs, using the UTAUT concept as a theoretical framework. The research method used is a survey of MSME actors in Denpasar City, using a questionnaire as a data collection tool involving 110 respondents. The sample in this study was determined by a non-probability method using a purposive sampling technique, with the criteria of implementing at least one payment gateway application. This sample was targeted at MSME actors in Endek, Denpasar City, who utilize the payment gateway system. The findings show that performance expectancy, effort expectancy, and social influence have a significant positive impact on the intention of MSME actors to use payment gateways. Trust, as a mediating variable, also shows a significant contribution in influencing the decision to adopt this technology. The digital ecosystem moderates the influence of trust on the intention to use. This study concludes that to increase the use of payment gateways among MSMEs, it is important for stakeholders to provide adequate education and support, as well as optimize existing digital infrastructure.